Climate change, ethics and sustainability: An innovative approach - José Luis Sánchez García; Juan María Díez Sanz (Journal of Innovation & Knowledge (JIK), 2018)
Our goal in this article is the analysis of the state of affairs, regarding the phenomenon of climate change and its impact in different areas. We synthesize the various approaches available in the scientific debate on this subject, mainly the one that affirms the existence of global warming and the current approach, which denies it. Beyond the controversy, what seems to be evident is that there is a multifactorial causality in a phenomenon that affects anthropogenic factors a well. Since some environmentalisms exclude the human being in their consideration of the ecosystem, and if they do, they accommodate man in their approaches always as a variable that distorts and deteriorates the environment, we believe that a fundamental rethinking of the issue is needed, from the perspective of an integral environmentalism. The environmentalism we propose not only does not exclude the human being from this multifactorial equation, but also considers man as the fundamental, modifiable variable in that process. We thus consider the environmental problem in the broader framework of an integral ecology, where the human being takes a central place, understood as a free person and a moral subject, responsible for his actions and a key element in any consideration and review of the process. In this context, the concept of sustainability emerges as a key concept that must guide human action in all areas, a concept from which it is possible to appeal to the responsibility of man within the framework of an ethics of sustainability. Man is called to do right in all orders. When he does not respect this ethical orientation, so implicitly included in his own conscience, he becomes denatured and suffers the consequences in himself and in the environment in which he lives. We believe that it is a priority to seek the foundations of the existence of God, analyzing the theistic view, the foundations of sustainability for the good of man himself and the planet.
Keywords: Q50; Q54; Q56; I3; Q01; 650; Climate change; Environment; Integral ecology; Sustainability; Ethics; Integral environmentalism; Theism